2020
DOI: 10.3390/coatings10010079
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Properties of Copper Nitride/Molybdenum Disulfide Composite Films Prepared by Magnetron Sputtering

Abstract: Cu3N/MoS2 composite films were prepared by magnetron sputtering under different preparation parameter, and their photocatalytic properties were investigated. Results showed that the composite films surface was uniform and had no evident cracks. When the sputtering power of MoS2 increased from 2 W to 8 W, the photocatalytic performance of the composite films showed a trend of increasing first and then decreasing. Among these films, the composite films with MoS2 sputtering power of 4 W showed the best photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Therefore, Cu 3 N nanostructures are combined with other semiconductors. For instance, Zhu et al demonstrated that the degradation of MO using TiO 2 @Cu 3 N thin films (effective band gap = 3.0 eV) is higher than in pure TiO 2 thin films, as seen in Figure 8b [35]. A degradation rate of 99.2% of MO solution with an initial concentration of 20 g/mL using a 500 W mercury lamp for 30 min was obtained [84].…”
Section: Photocatalytic Activity Of Cu 3 N Nanoparticlesmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, Cu 3 N nanostructures are combined with other semiconductors. For instance, Zhu et al demonstrated that the degradation of MO using TiO 2 @Cu 3 N thin films (effective band gap = 3.0 eV) is higher than in pure TiO 2 thin films, as seen in Figure 8b [35]. A degradation rate of 99.2% of MO solution with an initial concentration of 20 g/mL using a 500 W mercury lamp for 30 min was obtained [84].…”
Section: Photocatalytic Activity Of Cu 3 N Nanoparticlesmentioning
confidence: 98%
“…For example, TiO 2 -Cu 3 N nanocomposites manifest an improved bandgap compared to Cu 3 N alone. Zhu et al also reported the growth of TiO 2 -Cu 3 N and Cu 3 N-MoS 2 nanocomposite films by magnetron sputtering that demonstrate enhanced photocatalytic properties [35,84]. Both TiO 2 and MoS 2 are n-type semiconductors that, when combined with p-type Cu 3 N, create p-n junctions.…”
Section: Thin Film Deposition Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cu nanoparticles and their nanocomposites have been employed in degrading a wide range of analytes such as methylene blue, rhodamine B, methyl orange, 2-chlorophenol, bisphenol A, etc. (Basu et al 2014;Xu et al 2015;Talebi 2016;Zhu et al 2020).…”
Section: Traditional Photocatalystsmentioning
confidence: 99%